Study of Rhesus Genotype and Phenotype in Bangladeshi Population Attended in a Tertiary Care Hospital Transfusion Medicine (Anwer Khan Modern Medical College Journal, 2017)
Background: The Rhesus Blood Group is one of the most important Blood Group like ABO. Exposure of Rhesus Negative individuals to Rhesus Positive Red Cells by Transfusion and/or Pregnancy is most likely to stimulate the production of Rhesus antibodies. These Antibodies may cause Haemolytic Diseases of Newborn (HDN) and Delayed Haemolytic Transfusion Reaction (DHTR.) Rh-antigens, mainly D, C ,E, e and small c are well developed before birth. d is not present or used hypothetically. The frequency of these antigens can be determined by using five different antisera; anti-D,-C, small c, -E and small e. Based on these Phenotype and Gene frequencies in a particular Population, the most probable Rh Genotype can be determined.Methodology: This cross sectional comparative study was carried out with 1,000 randomized samples of both patient and donors in the department of Transfusion Medicine of Bangabandhu Sheikh Mujib Medical University (BSMMU). The eventual objective of the study was to determine the actual Rhesus phenotype-genotype frequency of Bangladeshi Native population. Sample was collected from both donor and patient. For each Test Saline and Anti Human Globulin Test (AHGT) were employed. Result: The most common genotype, we found, CDe/CDe i.e R1R1 (38.60%) which is the most vulnerable genotype to be immunized, the next group in our study was CDe/cde R1r(29.20%) and next category was CDe/Cde i.e. R1R2 (22.20%). Very rare genotype in our study detected was cDE/cde i.e. R2R (1.90%), cDE/cDE i.e. R2R2 (1.50%) CDE/cDE i.e.R1Rz (0.60%), cde/cde i.e. R0R0 (0.60%). Among Rh (D) Negative samples genotypes found is cde/cde i.e. rr (4.50%, and cde/cde i.e.r'r(0.8%) and Cde/cdE i.e. rr" (0.10%). Frequency distribution of genotype among male and female was also determined.Conclusion: The findings may be used in formulating Clinical Transfusion Practice and to fourmule strategies to prevent Rh Sensitization, may thus also be useful in disputed paternity and genetic study in Bangladesh.Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 25-28